2017
DOI: 10.3892/br.2017.951
|View full text |Cite
|
Sign up to set email alerts
|

Study and therapeutic progress on spinal cord perimedullary arteriovenous fistulas

Abstract: Abstract. Spinal cord perimedullary arteriovenous fistulas (PMAVFs) are rare and belong to type IV spinal cord arteriovenous malformations (AVMs). Little is known regarding the treatment and prognosis of spinal cord PMAVFs. In the present study the relevant literature from PubMed was reviewed, and it was found that these fistulas can occur at all ages but are more common in children. In children, most spinal cord PMAVFs are large and with high flow, begin with bleeding and are frequently associated with heredi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 74 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…[ 17 ] Endovascular treatment should be considered as second-line choice because of the difficulty in navigating a microcatheter through the long and tortuous course of the thin ASA; the possibility of reflux of the liquid embolic material into the ASA; the risk or tearing, dissecting, thrombosis, or vasospasm of the ASA during embolization; concerning about recanalization of the fistula; and requiring expertise and experience in neurointerventional procedure. [ 9 10 11 ] According to a review about treatment on spinal cord PMAVFs by Ji et al .,[ 18 ] they found that endovascular treatment is more effective in high-flow PMAVFs, leading to a good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Endovascular treatment should be considered as second-line choice because of the difficulty in navigating a microcatheter through the long and tortuous course of the thin ASA; the possibility of reflux of the liquid embolic material into the ASA; the risk or tearing, dissecting, thrombosis, or vasospasm of the ASA during embolization; concerning about recanalization of the fistula; and requiring expertise and experience in neurointerventional procedure. [ 9 10 11 ] According to a review about treatment on spinal cord PMAVFs by Ji et al .,[ 18 ] they found that endovascular treatment is more effective in high-flow PMAVFs, leading to a good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…When the first symptoms appear, there is a 50% probability of progression to a bed-ridden state (Aminoff 5) within 3 years [ 7 ]. Therefore, timely recognition of the sAVF is essential to allow therapy to meet a narrow window of opportunity [ 3 ]. Less frequently, the symptoms of PMAVF may be caused by rupture and hemorrhage either in the intramedullary or in the subarachnoid space [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, intramedullary hemorrhage or subarachnoid hemorrhage (SAH) may occur as well [ 1 ]. Magnetic resonance imaging (MRI) of the spine and spinal angiography may elucidate the type of lesion and the proper treatment modality can be selected [ 2 , 3 , 4 ]. However, the initial clinical manifestation can be nonspecific and may mislead the initial diagnosis; the exact diagnosis may become apparent only after more severe and specific clinical manifestation transpire [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…PAVFs result from direct communication between feeding arteries and enlarged draining veins without the intervening nidus; they are intradural but extramedullary, and in the cervical region, they are usually located on the anterior or lateral surface of the spinal cord ( 56 ). The shunting points can be single or multiple ( 57 ). Cervical PAVFs are not uncommon; in the Mizutani et al, study, PAVFs in the cervical region accounted for 22.4% of all PAVFs ( 2 ).…”
Section: Cervical Spinal Avfsmentioning
confidence: 99%
“…Not all PAVFs are appropriate for EVT. For Type A PAVFs, EVT is difficult because ASA catheterization is problematic; for Types B and C PAVFs, transarterial EVT via the ASA may be a safe and effective choice ( 57 , 63 ). Certainly, if the ASA is a bystander in PAVFs, EVT is easy ( Figure 3 ).…”
Section: Cervical Spinal Avfsmentioning
confidence: 99%